Extragasteral Manifestations of Helicobacter Pylori Associated Gastroduodenal Pathology in Children (Eurasian Medical Research Periodical, 2022)
Recently, there has been evidence of extragastric manifestations of Helicobacter pylori infection, in particular, participation in the development of allergic pathology, which can be attributed to the high prevalence of Helicobacteriosis in children with food allergies The systemic nature of lesions of the gastrointestinal tract (GIT) in allergy causes a frequent combination of symptoms of damage to the upper and lower parts of the digestive tract and, therefore, makes it appropriate to study the digestive function of the intestine and its microbiocenosis